x^2 = 4 x
solution 1, x = 0
then x = 4, so we have
solution 2, x = 4.
2007-01-19 03:20:47
·
answer #1
·
answered by Jano 5
·
1⤊
0⤋
x= 0 ,4
2007-01-19 03:20:49
·
answer #2
·
answered by rajeev_iit2 3
·
0⤊
0⤋
x - 2sqrt(x) = 0
Add 2 sqrt(x) to both sides
x = 2 sqrt(x)
Squaring both sides
x*2 = 4x
Subtracting 4x from both sides and factorizing
x . (x - 4) = 0
Hence, x = 0 and (x - 4) = 0
x = 0 and x = 4
Note: please check by plugging if the values of x are valid. When you square both sides, there is a possibility that an extraneous value may come out which will not satisfy the equation. Here both values are valid.
2007-01-19 03:26:33
·
answer #3
·
answered by Sheen 4
·
0⤊
0⤋
The answer is 0, 4.
Now, how did they do that?
x - 2x^(1/2) = 0, multiply both sides of the equation by (x + 2x^(1/2))
(x-2x^(1/2)) (x+2x^(1/2)) = 0 (x-2x^(1/2))
x^2 - 4x = 0, now factor out the x
x(x-4) = 0
x = 0, x = 4
Check the work by plugging the answers back in...hope this helps
2007-01-19 03:25:45
·
answer #4
·
answered by Rockit 5
·
0⤊
0⤋
you can write x=2sqrt x (Consider xmust be >=0) Squaring both sides x^2=4x ==> x(x-4)=0 so x=0 ,x=4
2007-01-19 05:26:36
·
answer #5
·
answered by santmann2002 7
·
0⤊
0⤋
Factor in terms of sqrtx:
sqrtx(sqrtx-2) = 0
→ sqrtx = 0 or sqrtx = 2
→ x=0 or x=4.
2007-01-19 03:53:39
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
x - 2 sqrt(x) = 0
x = 2 sqrt(x)
x/2 = sqrt(x) ... Now sqaure both sides:
(x/2) * (x/2) = x
(1/4) x² = x ... Now rearrange terms
(1/4) x² - x = 0 ... Solve this quadratic.
... First kill the Fraction (mult. by 4)
x² - 4x = 0 ... Complete the Square
2007-01-19 03:42:12
·
answer #7
·
answered by Razor 2
·
0⤊
0⤋
you write x-2sqrt x =0
x=2sqrt x
square this
x^2 = 4x ---> x(x-4) =0
roots x=0 x=4
It works !
2007-01-19 03:23:42
·
answer #8
·
answered by maussy 7
·
0⤊
0⤋
put the entire equation to the second power, then you have:
x-squared - 4x = 0, which should be easier to solve.
2007-01-19 03:21:47
·
answer #9
·
answered by AH 3
·
0⤊
1⤋